Targeting the Microglial NLRP3 Inflammasome and Its Role in Parkinson's Disease. Issue 1 (4th November 2019) - Haque, Md. Ezazul; Akther, Mahbuba; Jakaria, Md.; Kim, In‐Su; Azam, Shofiul; Choi, Dong‐Kug
Abstract: Excessive activation of microglia and subsequent release of proinflammatory cytokines play a crucial role in neuroinflammation and neurodegeneration in Parkinson's disease (PD). Components of the nucleotide‐binding oligomerization domain and leucine‐rich‐repeat‐ and pyrin‐domain‐containing 3 inflammasome complex, leucine‐rich‐repeat‐ and pyrin‐domain‐containing 3, caspase‐1, and apoptosis‐associated speck‐like protein containing a CARD, are highly expressed in activated microglia in PD patient brains. Findings suggest that neurotoxins, aggregation of α‐synuclein, mitochondrial reactive oxygen species, and disrupted mitophagy are the key regulators of microglial leucine‐rich‐repeat‐ and pyrin‐domain‐containing 3 inflammasome activation and release of interleukin‐1β and interleukin‐18 caspase‐1‐mediated pyroptotic cell death in the substantia nigra of the brain. Although this evidence suggests the leucine‐rich‐repeat‐ and pyrin‐domain‐containing 3 inflammasome may be a potential drug target for treatment of PD, the exact mechanism of how the microglia sense these stimuli and initiate leucine‐rich‐repeat‐ and pyrin‐domain‐containing 3 inflammasome signaling is unknown. Here, the molecular mechanism and regulation of microglial leucine‐rich‐repeat‐ and pyrin‐domain‐containing 3 inflammasome activation and its role in the pathogenesis of PD are discussed. Moreover, the potential of both endogenous and synthetic leucine‐rich‐repeat‐ and pyrin‐domain‐containing 3 inflammasome modulators, long noncoding RNA, microRNA to develop novel therapeutics to treat PD is presented. Overall, we recommend that the microglial leucine‐rich‐repeat‐ and pyrin‐domain‐containing 3 inflammasome can be a potential target for PD treatment. © 2019 International Parkinson and Movement Disorder Society